Resourceful earth - "Simon, Jullian L. (ed.)" (New York, 1984)
Predicts what the world will be like at the turn of the century in terms of agriculture, world population, water resources, climate, minerals, oil, nuclear power, environmental quality, nutrition, and health
Keywords: "Economic history, 1971 - 2000"